ANALYSIS OF ACTIVE LEARNING IN SCHOOL (ALIS) ON BIOLOGY SUBJECT AT SENIOR HIGH SCHOOL IN SALATIGA - Priyayi, Desy Fajar; Situmorang, Risya Pramana; Airlanda, Gamaliel Septian (Prodi Teknologi Pendidikan, 2016)
Abstract, Active learning in school (ALIS) is one of the learning models that can be applied by teachers to improve students’ achievement. This study aims to determine the implementation of ALIS indicator on biology subject at senior high school in Salatiga and to know the factors that influence it. This is a descriptive qualitative research and the data was collected using questionnaires, observation, interview, and documentation technique. The objects of study were 156 students and 5 biology teachers at five senior high schools in Salatiga. The results showed the percentage of ALIS indicators from low level to high were: learning to encourage students to interact multidirectional (60.42%); using the environment as a medium and learning resources (64.94%); maintaining the learning environment (65.81%); learning encourages student to think at high level (66.11%); student-centered learning (66.91%); there are feedback on student work (70.47%); monitoring the learning process by teacher (71.04 %); contextual learning (73.63%); learning model accommodate different learning style (75.71%). Biology teachers in Salatiga have been implementing ALIS but there are some factors influence it which include lack of time to study with so many subject materials, inadequate facilities and infrastructure, and the students’ unfamiliarity with the application of active learning.Keywords: ALIS, active learning, biology teaching and learningAbstrak, Active learning in school (ALIS) merupakan salah satu pilihan model pembelajaran yang dapat diterapkan oleh guru dan memberikan dampak positif kepada siswa. Penelitian ini bertujuan untuk mengetahui penerapan indikator ALIS pada mata pelajaran biologi sekolah menengah atas (SMA) di Salatiga dan faktor-faktor yang mempengaruhinya. Penelitian ini merupakan penelitian deskriptif kualitatif dengan teknik pengumpulan data menggunakan angket, observasi, wawancara dan dokumentasi. Obyek penelitian adalah 156 siswa dan 5 guru biologi yang tersebar di lima Sekolah Menengah Atas (SMA) kota Salatiga. Hasil penelitian menunjukkan persentase keterlaksanaan indikator ALIS dari tingkat rendah ke tinggi adalah: pembelajaran mendorong siswa untuk berinteraksi multiarah (60,42%), pembelajaran penggunaan lingkungan sebagai media dan sumber belajar (64,94%), adanya penataan lingkungan belajar (65,81%), pembelajaran mendorong anak untuk berpikir tingkat tinggi (66,11%), pembelajaran berpusat pada siswa (66,91%), adanya umpan balik terhadap hasil kerja siswa (70,47%), pemantauan proses belajar oleh guru (71,04%), pembelajaran terkait dengan kehidupan nyata (73,63%), pembelajaran mengakomodasi gaya belajar yang berbeda-beda (75,71%).Guru biologi di Salatiga telah melaksanakan ALIS, namun terdapat beberapa hambatan antara lain: keterbatasan waktu dengan tuntutan banyaknya materi, terbatasnya sarana dan prasarana, dan belum terbiasanya siswa menerapkan pembelajaran aktif.